Pengaruh Disiplin terhadap Kinerja Pegawai Kantor Ketahanan Pangan Kabupaten Sumedang - Sudrajat, Arip Rahman (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2017)
The purpose of this study was to determine factor that influence employee performance toward employee discipline in Food Security Office of Sumedang. The method employed is descriptive analysis. By using saturated sampling, this research population includes 30 respondents. Data were collected by literature study, questionnaires, observations and interviews. This research employs data analysis techniques such as correlation coefficient test, significance test and coefficient of determination. The results showed that the level of employee discipline in Food Security Office of Sumedang reached 78.76 percent and the rate of employee performance reached 80.86 percent. While the relationship between discipline and employee performance in District Food Security Office of Sumedang shows correlation coefficient of 0.73 which is in the strong category. The influence on employee performance discipline in Food Security Office of Sumedang reached 53.29 percent, the remaining 46.71 percent is influenced by other factors not examined